The Effect of Cutoffs on the Uplift Pressure Beneath the Hydraulic Structures Floor - Faisal Al Tabatabaie; Dhabia Sabeeh Al Waily (Wasit Journal of Engineering Sciences)
The use of cutoffs underneath the hydraulic structures is considered a safe solution to ensure the stability of hydraulic structure against uplift pressure and piping phenomenon in addition to the sliding and overturning forces of the water. These cutoffs are used at critical sections underneath the floor of hydraulic structure to substitute with their depths the horizontal lengths of the creep line of the hydraulic structure base. In this paper, the experimental method- by using electrical analogue model- was carried out to plot the flow net and study the efficiency of the front and rear faces of the cutoffs for dissipating the potential energy of the percolating water underneath the floor of hydraulic structure. An electrical analogue model which was used in this study consists of twenty five models with different depths of upstream and downstream cutoffs. After plotting the flow net for all models, it is concluded that the efficiency of the inner sides are less than that of the outer sides which were investigated before in this topic of this work that both faces reduction values in the uplift pressure are considered the same, where the efficiency of the outer face of upstream cutoff is (70.35) % and for the inner face is (29.64)%, while for the downstream cutoff the efficiency for the outer face is (76.21)% and for the inner face is (23.79)% .